Digitalisierung beruflicher Lern- und Arbeitsprozesse Impulse aus der Bauwirtschaft und anderen gewerblich-technischen Sektoren - Appenrodt, Jan (Universitätsverlag der Technischen Universität Berlin, 2022)
The anthology "Digitization of professional learning and working processes - impulses from the construction industry and other commercial-technical sectors" presents current approaches to digitally supported professional learning. The articles provide insights into the dynamic development of the interfaces between gainful employment and vocational training and further education in the context of digitization of work and learning aids. The volume is thus connected to the publication "Berufsbildung am Bau digital" (edited by Bernd Mahrin and Johannes Meyser), which was published in 2019 by the University Press of the Technische Universität Berlin. The first chapter discusses fundamental didactic questions about digitally supported learning and working, including the framework conditions. The second chapter picks contributions on capacity development, standards, and digital tools out as central themes. The third chapter is dedicated to concrete specific solutions with strong practical relevance and high transfer potential for digitized work and learning in the construction sector and in the metal sector. The final fourth chapter presents comprehensive and freely accessible online offers such as a media pool for educational purposes, a learning media database and a hybrid learning system with a virtual 3D building model. The book was created as part of the DigiBAU project - digital vocational learning and working in the field of construction - funded by the German Federal Ministry of Education and Research and the European Social Fund.